Parietal and occipital lobe contributions to perception of straight ahead orientation - Ferber, S. (BMJ Group, 1999)
OBJECTIVES—Several studies have investigated how peripheral stimulation affects the perception of body orientation in healthy subjects. The studies showed that opposing stimulation of two different input modalities can cancel out, leaving perception of body orientation unchanged. It was ascertained whether a comparable phenomenon could be found in brain damaged patients with two distinct disorders which individually lead to opposing shifts of the perceived midline. METHODS—The visual subjective straight ahead was measured in patients with pure neglect, pure hemianopia, or a combination of neglect and hemianopia. RESULTS—As in previous studies, patients with pure neglect displayed an ipsilesional displacement of the perceived straight ahead. Patients with pure hemianopia showed a contralesional shift. By contrast, no significant midline shift occurred in the patients with both neglect and hemianopia. CONCLUSIONS—Neglect and hemianopia interact so that opposing biases in the perception of body orientation neutralise each other. Both parietal and occipital areas seem to contribute to the perception of straight ahead body orientation and seem to have counteracting effects when lesioned in the same hemisphere.